Reference conditions and modification factors for the standardization of nondestructive variables used in the evaluation of existing timber structures. (30th December 2015) - Íñiguez-González, Guillermo; Arriaga, Francisco; Esteban, Miguel; Llana, Daniel F.
Abstract: The main objective of this paper is to define the reference conditions and to propose modification factors to standardize the variables recorded by different nondestructive techniques. This practice will make it possible to generate consistent practical data while developing a procedure for the standardization of timber structure assessment. The nondestructive variables analyzed are: time of flight, natural frequency, pullout resistance, penetration depth and drill resistance. The factors which affect these variables are: moisture content, temperature, size/length and positioning of sensors and angle to the grain. Reference conditions are defined and equations and modifications factors are proposed to help in the evaluation of existing timber structures and decision making.